'I'm waiting for that': Interest in the use of PrEP for safer conception in Botswana. Issue 8 (2nd August 2020) - Gutin, Sarah A.; Harper, Gary W.; Amico, K. Rivet; Bitsang, Christina; Moshashane, Neo; Harries, Jane; Ramogola-Masire, Doreen; Morroni, Chelsea
ABSTRACT: Safe and effective low-cost safer conception (SC) methods are increasingly available and being integrated into national guidelines in sub-Saharan African contexts. Sero-different couples of childbearing age can benefit from such services and the routine provision of SC counselling. Pre-exposure prophylaxis (PrEP) to prevent HIV acquisition to uninfected partners can reduce the chances of HIV transmission when trying to achieve pregnancy. Botswana has a strong commitment to reducing new HIV infections but PrEP is not yet widely available and little guidance has been offered on counselling sero-different couples. We conducted qualitative in-depth interviews in Gaborone, Botswana with 10 HIV healthcare providers and 10 women living with HIV of childbearing age because they act as a key conduit for reaching sero-different partners with information about PrEP. We examined knowledge and attitudes towards PrEP to assess the viability and develop a deeper understanding of this SC option. Interviews were analysed using an interpretive phenomenological approach. Three themes emerged: (1) awareness of PrEP is limited, (2) providers and women overwhelmingly showed interest in PrEP and (3) women living with HIV and providers have concerns about PrEP use. With the correct support, PrEP could be a useful SC option for sero-different couples in Botswana and other sub-Saharan contexts.